ERROR ANALYSIS ON THE USE OF TO BE AS AUXILIARY AND LINKING VERB IN THE STUDENTS’ RECOUNT TEXT (A Case of the 8th Grade Students of SMP N 19 Semarang in the Academic Year of 2013/2014) (ELT Forum: Journal of English Language Teaching, 2014)
This final project was conducted to analyze the students’ errors on the use of to be as Auxiliary and Linking verb on the students’ recount text that made by eight grade students of SMP N 19 Semarang in the academic year of 2013/2014. This study has three objectives; i.e. to identify errors, to find out the most frequent errors and how to avoid errors on the use of to be as auxiliary and linking verb. The population of this study was eighth grade students of SMP N 19 Semarang. This study used purposive random sampling and one class had been taken as the sample under the consideration that the number of the sample was about 10% - 15% from the population. I chose class 8B which consist 31 students, but only 28 students could participate on the research. This study used qualitative research method in analyzing the data since the aim of the study is to identify errors, to find out the error, type and how to avoiding error on the use of to be as Auxiliary and Linking verb. In gathering the data, I conducted the instructions for the students’ free writing using some topics that had been prepared before the research on 10 may 2013. To find out the errors, I used the error taxonomy according Dulay, Burt and Krashen (1980:50). I classified the errors into 4 types that are Omission, addition, misinformation and misordering. The result showed that 11.3 % from the total findings belongs to errors on the use of Auxiliary verb which consisted of 8.1 % in misinformation types and 3.2 % in omission types and 88.7 % from the total findings belongs to errors on the use of Linking verb which consisted of 45.2 % in misinformation types, 20.9 % in omission types, 19.4 % in addition types and 3.3 % in misordering types. After analyzing and counting the data, I found out that the most frequent errors were errors on the use of Linking verb which were dominated by misinformation types.